Cultural Taboos and Women’s Reproductive Health: A Sociological Analysis of Menstruation Beliefs - Samina Aziz; Dr. Amber Ferdoos (Journal of Religion and Society, 2025)
This paper explores the role of menstrual taboos in influencing the knowledge of women, their day-to-day activities, and their social involvement in different cultural and socioeconomic settings. Based on semi-structured qualitative interviews of 16 to 40 years old women, the results indicate that the process of menstruation is usually enveloped with silence, modesty and stigma. The respondents were found to have a few or false knowledge based on cultural beliefs rather than formal schooling. Menstrual products were available depending on economic status but the stigma was common among groups. Restrictions on religious and social participation were widely practiced and understood as cultural expectations. The study concludes that menstrual taboos continue to limit agency and reinforce gendered norms, highlighting the need for culturally sensitive education, open dialogue, and policy-level interventions to promote menstrual dignity and inclusion. Keywords: Menstrual Health, Fertility Beliefs, Infertility Stigma, Cultural Taboos, Reproductive Health, Gender Norms